Genome-wide selection signal analysis reveals copy number variation associated with litter size in Guizhou Black goat - Zhao, Yanpin; Han, Yong; Yuan, Chao; Yang, Yang; Long, Yong; Xiao, Wen (Frontiers in Veterinary Science, 2025)
IntroductionCopy number variation (CNV) is a common form of genomic structural variation arising from genome sequence rearrangements, which primarily involves variations in the copy number of large genomic segments. This study focuses on performing selection signal analysis of CNVs to identify candidate loci and genes associated with litter size in Guizhou Black goat.MethodsSample selection: 30 Guizhou Black goats were divided into high-lambing and low-lambing groups based on their continuous lambing records. Genetic analysis: Phylogenetic tree construction and principal component analysis (PCA) were performed to assess genetic differences between the two groups. Selection signal indicators: Genetic differentiation index (FST) and nucleotide diversity (θπ) were used as indicators for identifying selection signals. CNV identification: 180 CNVs associated with litter size were identified through selection signal analysis. Functional annotation: Candidate genes within these CNVs were annotated, and further analysis was conducted using Gene Ontology (GO) and KEGG pathway enrichment methods.ResultsGenetic differentiation: Phylogenetic tree construction and PCA revealed significant differences in genetic structure between the high-lambing and low-lambing groups. CNV identification: 180 CNVs were found to be associated with litter size. Candidate genes: Functional annotation of the CNVs identified 49 candidate genes. Pathway enrichment: GO and KEGG pathway analysis revealed significant enrichment of these genes in several reproduction-related biological pathways, including the Hippo signaling pathway, steroid hormone biosynthesis, and retinol metabolism.DiscussionThis study provides novel insights into the genetic mechanisms underlying prolificacy in Guizhou Black goats. The identification of CNVs associated with litter size offers potential targets for genomic selection breeding, which could be used to improve reproductive traits in this breed. The enriched pathways, such as the Hippo signaling pathway, steroid hormone biosynthesis, and retinol metabolism, suggest that these biological processes may play a critical role in regulating fertility and reproductive efficiency in goats. The findings highlight the potential for utilizing CNVs as markers for improving reproductive performance in livestock breeding programs.